Nasal airflow comparison in neonates, infant and adult nasal cavities using computational fluid dynamics - Corda, John Valerian; Shenoy, B. Satish; Ahmad, Kamarul Arifin; Lewis, Leslie; K., Prakashini; Abdul Khader, S. M.; Zuber, Mohammad (Elsevier, 2022)
Background and objective: Neonates are preferential nasal breathers up to 3 months of age. The nasal anatomy in neonates and infants is at developing stages whereas the adult nasal cavities are fully grown which implies that the study of airflow dynamics in the neonates and infants are significant. In the present study, the nasal airways of the neonate, infant and adult are anatomically compared and their airflow patterns are investigated. Methods: Computational Fluid Dynamics (CFD) approach is used to simulate the airflow in a neonate, an infant and an adult in sedentary breathing conditions. The healthy CT scans are segmented using MIMICS 21.0 (Materialise, Ann arbor, MI). The patient-specific 3D airway models are analyzed for low Reynolds number flow using ANSYS FLUENT 2020 R2. The applicability of the Grid Convergence Index (GCI) for polyhedral mesh adopted in this work is also verified. Results: This study shows that the inferior meatus of neonates accounted for only 15% of the total airflow. This was in contrast to the infants and adults who experienced 49 and 31% of airflow at the inferior meatus region. Superior meatus experienced 25% of total flow which is more than normal for the neonate. The highest velocity of 1.8, 2.6 and 3.7 m/s was observed at the nasal valve region for neonates, infants and adults, respectively. The anterior portion of the nasal cavity experienced maximum wall shear stress with average values of 0.48, 0.25 and 0.58 Pa for the neonates, infants and adults. Conclusions: The neonates have an underdeveloped nasal cavity which significantly affects their airway distribution. The absence of inferior meatus in the neonates has limited the flow through the inferior regions and resulted in uneven flow distribution.